Korelasi Sains Dan Teknologi Dengan Alkitab Dan Iman Kristen Di Tengah Kehidupan Orang Percaya - Agustian, Daniel Ferry; Suhadi (Sekolah Tinggi Teologi Sriwijaya, 2024)
Science and technology are often opposed to the Bible and faith, both by Christians and non-Christians. Many people think that the Bible and Christian faith have no correlation. Even more so, secular people tend to despise the values ​​contained in the Bible and the Christian faith. Various methods and methods were developed and carried out to doubt and discredit the Bible and the Christian faith. Moreover, in the current context, the Bible and the Christian faith are seen as outdated and no longer relevant to the current context of human life. They think that the Bible and the Christian faith cannot answer human needs today because they have no correlation at all. To answer the view above, the researcher attempts to show that in the real world, both in the past and in the present, the Bible and the Christian faith remain relevant to the context of human life in all times. That the Bible and Christian faith have a close correlation with science and technology. The truth of science and technology is not only supported by the Bible, but the Bible can also be used as a foundation in efforts to think and search for truth in science and technology.This research was conducted using qualitative methods and literature study, namely research with descriptive analytical presentation. Data was compiled and obtained through literature studies sourced from research results, books and journals which were then analyzed descriptively and presented in writing in the form of a scientific journal about The Correlation Of Science And Technology With The Bible And Christian Faith In The Lives Of Believers.